EFECTO REMINERALIZANTE IN VITRO DE DOS COLUTORIOS EN EL ESMALTE DE MOLARES PERMANENTES DESMINERALIZADOS - Rodríguez-Chávez, Daniela Soledad (2026)
Objective: To compare the in vitro remineralizing effect of two mouthwashes on the enamel　of demineralized permanent molars. Materials and methods: The study was experimental and　conducted in vitro. Twenty healthy third molars were used. They were randomly divided into　two groups (xylitol mouthwash vs. fluoride mouthwash). After demineralizing the tooth crowns　with 37% orthophosphoric acid, they were immersed in the mouthwash treatments at 37 °C for　15, 30, and 45 days, with mouthwash replacement every 3 days. The degree of remineralization　was evaluated in 150-250 μm sections under a polarized light microscope (EUROTECH), using　the following scale: 0 (no change), 1 (superficial), 2 (sub superficial), and 3 (deep). The Mann-Whitney U test, Friedman test, and Holm post hoc test were used (p < 0.05). Results: The fluoride　mouthwash showed significantly higher remineralization Grades than xylitol at all time intervals:　at 15 days, 60% vs. 30% grade 1 (p = 0.481); at 30 days, 20% grade 1, 60% grade 2, and 20% grade 3 vs. 50% grade 1 and 10% grade 2 (p = 0.052); and at 45 days, 60% grade 3, 40% grade 2 vs. 30% grade 1 and 30% grade 2 (p = 0.043). Both treatments showed significant evolution over time (p =0.001), but only fluoride reached its maximum effect at 45 days. Conclusion: Both mouthwashes　showed a remineralizing effect on demineralized enamel; however, fluoride had a significantly superior effect.